Podoba slovenskih splošnih knjižnic v letu 2007 - Vodeb, Gorazd (Knjižnica, 2008)
Article presents statistical data about slovenian public libraries in 2007. Data were collected by Library System Development Center at National & University Library. 61 administrative units had 1062 service points including mobile library stops. Figures indicate opening times, space and equipment, size of libraries' collections and additions. Staff structure and finances are also presented beside data about visitors, registered members, loans and other library services. Indicators are compared to requirements of library regulations and standards, progress in reaching goals of Resolution on the 2004-2007 National Programme for Culture is also evaluated.
Keywords: splošne knjižnice; statistični podatki; Slovenia; Slovenija; 2007